Empowerment Evaluation’s Practice and Principle Effects on Psychological Empowerment and Self-Determination Outcomes - Sheldon, Jeff (Journal of Organizational Psychology, 2024)
This study contributed to a limited body of research on empowerment evaluation by examining its processes, principles, and outcomes. Objectives included: 1) determining implementation fidelity to the three empowerment evaluation models; 2) determining evidence of empowerment evaluation process principles; 3) determining whether empowerment evaluation outcome principles resulted from the evaluations reported on; and 4) determining whether variation in empowerment and self-determination was explained by the interaction between model fidelity and percentage of steps implemented, process principles in evidence, outcome principles in evidence, and evaluator characteristics. Results indicated individual empowerment and self-determination were likely outcomes of evaluations reported on; evidence of all ten empowerment evaluation principles indicated they were empowerment evaluations; evaluators adhered with fidelity to all three models, no model was privileged over another, and steps were chosen from across all three models. Empowerment and self-determination are more likely when empowerment evaluations are conducted by female evaluators living and working in an African country and SEEPPO was a successful first attempt at assessing the process and outcomes of empowerment evaluation work.